Next generation sequencing and sequence assembly methodologies and algorithms - Masoudi-Nejad, Ali., (SpringerBriefs in systems biology,, 2013)
The goal of this book is to introduce the biological and technical aspects of next generation sequencing methods, as well as algorithms to assemble these sequences into whole genomes. The book is organized into two parts; part 1 introduces NGS methods and part 2 reviews assembly algorithms and gives a good insight to these methods for readers new to the field. Gathering information, about sequencing and assembly methods together, helps both biologists and computer scientists to get a clear idea about the field. Chapters will include information about new sequencing technologies such as ChIp-seq, ChIp-chip, and De Novo sequence assembly. Preface -- Next generation sequencing methodologies -- Emergence of next generation sequencing -- Assembly of sequencing data -- De novo assembly algorithms -- Index.